2016
DOI: 10.1016/j.freeradbiomed.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial impairments contribute to Spinocerebellar ataxia type 1 progression and can be ameliorated by the mitochondria-targeted antioxidant MitoQ

Abstract: Mitochondrial impairments contribute to Spinocerebellar ataxia type 1 progression and can be ameliorated by the mitochondria-targeted antioxidant MitoQ, Free Radical Biology and Medicine, http://dx.doi.org/10.1016/j.freeradbiomed.2016.07.005 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting galley proof befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 76 publications
2
65
0
Order By: Relevance
“…Mutant ATXN1 can affect the stability of RAR-related orphan receptor alpha (ROR α ), which plays an important role in Purkinje cell functions. Decreased gene expression of RORα has been associated with ataxia and cerebellar hypoplasia [134, 135]. …”
Section: Oxidative Stress In Spinocerebellar Ataxia Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…Mutant ATXN1 can affect the stability of RAR-related orphan receptor alpha (ROR α ), which plays an important role in Purkinje cell functions. Decreased gene expression of RORα has been associated with ataxia and cerebellar hypoplasia [134, 135]. …”
Section: Oxidative Stress In Spinocerebellar Ataxia Diseasementioning
confidence: 99%
“…While most types of SCAs are suggested as genetic diseases correlated with ATXN mutation, other pathogenic mechanisms that involve the dysfunction of mitochondria have been proposed [134, 135]. Hakonen et al observed respiratory complex I deficiency and mitochondrial DNA depletion in the brain of infantile-onset SCA individuals [136].…”
Section: Oxidative Stress In Spinocerebellar Ataxia Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, the other SCA1 mouse model, SCA1 154Q/2Q (Watase et al, ) and the transgenic mice for AFG3L2, the gene responsible for autosomal dominant SCA28 (Di Bella et al, ), display cerebellar mitochondrial dysfunction at histochemical and molecular level (Maltecca et al, ; Stucki et al, ).…”
Section: Discussionmentioning
confidence: 99%